Initial response of young people with thyrotoxicosis to block and replace or dose titration thionamide. Issue 1 (1st January 2022) - Wood, Claire L; Morrison, Niamh; Cole, Michael; Donaldson, Malcolm; Dunger, David B; Wood, Ruth; Pearce, Simon H S; Cheetham, Timothy D
Abstract : Objective: Patients with thyrotoxicosis are treated with anti-thyroid drug (ATD) using block and replace (BR) or a smaller, titrated dose of ATD (dose titration, DT). Design: A multi-centre, phase III, open-label trial of newly diagnosed paediatric thyrotoxicosis patients randomised to BR/DT. We compared the biochemical response to BR/DT in the first 6 months of therapy. Methods: Patients commenced 0.75 mg/kg carbimazole (CBZ) daily with randomisation to BR/DT. We examined baseline patient characteristics, CBZ dose, time to serum thyroid-stimulating hormone (TSH)/free thyroxine (FT4) normalisation and BMI Z-score change. Results: There were 80 patients (baseline) and 78 patients (61 female) at 6 months. Mean CBZ dose was 0.9 mg/kg/day (BR) and 0.5 mg/kg/day (DT). There was no difference in time to non-suppressed TSH concentration; 16 of 39 patients (BR) and 11 of 39 (DT) had suppressed TSH at 6 months. Patients with suppressed TSH had higher mean baseline FT4 levels (72.7 vs 51.7 pmol/L; 95% CI for difference 1.73, 31.7; P = 0.029). Time to normalise FT4 levels was reduced in DT (log-rank test, P = 0.049) with 50% attaining normal FT4 at 28 days (95% CI 25, 32) vs 35 days in BR (95% CI 28, 58). Mean BMI Z-score increased from 0.10 to 0.81 at 6 months (95% CI for difference 0.57, 0.86; P < 0.001) and was greatest in patients with higher baseline FT4 concentrations. Conclusions: DT-treated patients normalised FT4 concentrations more quickly than BR. Overall, 94% of patients have normal FT4 levels after 6 months, but 33% still have TSH suppression. Excessive weight gain occurs with both BR and DT therapy.